Working in Groups: The Importance of Communication in Developing Trust and Cooperation - Bryan D. Terry (EDIS)
Working together in groups can be a great experience or one filled with stress and anxiety. The success of group work depends largely on the trust developed among group members and the respect they show each other. When an individual has had a positive experience in a group, he/she is more likely to take risks, ask questions, and share ideas that will benefit the total group. This 3-page fact sheet was written by Bryan D. Terry, and published by the UF Department of Family Youth and Community Sciences, August 2013. http://edis.ifas.ufl.edu/fy1378